2021
DOI: 10.3390/ijms221910892
|View full text |Cite
|
Sign up to set email alerts
|

Salt Stress Promotes Abscisic Acid Accumulation to Affect Cell Proliferation and Expansion of Primary Roots in Rice

Abstract: The primary root is the basic component of the root system and plays a key role in early seedling growth in rice. Its growth is easily affected by environmental cues, such as salt stress. Abscisic acid (ABA) plays an essential role in root development, but the molecular mechanism underlying ABA-regulated root growth in response to salt stress remains poorly understood. In this study, we report that salt stress inhibits primary root elongation and promotes primary root swelling. Moreover, salt stress induces th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 57 publications
3
17
0
Order By: Relevance
“…In this study, the pathway "plant hormone signal transduction" was significantly enriched in the R7 leaf, which included 23 DEGs related to auxin, cytokinin, gibberellin, abscisic acid, ethylene, and salicylic acid. Our results were consistent with the previous studies showed that these hormones play irreplaceable roles in the response to salt stress in plants (Zheng et al, 2018;Feng et al, 2019;Gao et al, 2021;Huang et al, 2021;Saini et al, 2021;Zhu et al, 2021). For instance, salt stress can induce ABA signaling and activate an ABA-dependent responsive complex to cope with saline stress in plants (Umezawa et al, 2009;Cai et al, 2017;Soma et al, 2017;Lin et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the pathway "plant hormone signal transduction" was significantly enriched in the R7 leaf, which included 23 DEGs related to auxin, cytokinin, gibberellin, abscisic acid, ethylene, and salicylic acid. Our results were consistent with the previous studies showed that these hormones play irreplaceable roles in the response to salt stress in plants (Zheng et al, 2018;Feng et al, 2019;Gao et al, 2021;Huang et al, 2021;Saini et al, 2021;Zhu et al, 2021). For instance, salt stress can induce ABA signaling and activate an ABA-dependent responsive complex to cope with saline stress in plants (Umezawa et al, 2009;Cai et al, 2017;Soma et al, 2017;Lin et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…ABA, which regulates salt stress-responsive gene expression, is the central regulator of salt tolerance, and the application of ABA could mimic the effects of various stresses on plants [ 35 ]. Moreover, ABA plays a crucial role in the processes of seed germination and root development [ 36 , 37 ]. To study whether BcWRKY33A responds to ABA, we examined the seed germination and root growth of WT and 35S:BcWRKY33A-GFP transgenic lines under various ABA concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…In Stylosanthes humilis , salt stress led to increased ABA production and decreased seed germination; however, when seeds were treated with ABA biosynthesis inhibitors, the negative effects of salt stress on seed germination were partially relieved or eliminated [ 36 ]. In rice, under salt stress conditions, ABA-responsive genes were induced and endogenous ABA accumulated; these factors inhibited the vertical elongation of the primary roots [ 37 ], which suggests that tolerance to ABA is closely related to the salt tolerance of plants. When treated with high concentrations of ABA, lines #1 and #4 exhibited a higher germination rate and longer root lengths than the WT ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the maintenance of root growth is generally related to salt tolerance. Salt stress can affect rice root growth by reducing proliferating activity of meristematic cells [ 53 ]. Consistently, the data reported here shows that rice-root cells experienced cell cycle impairment under salt stress.…”
Section: Discussionmentioning
confidence: 99%